2000
DOI: 10.1634/theoncologist.5-6-454
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Differentiation and Apoptosis— A Possible Strategy in the Treatment of Adult Acute Myelogenous Leukemia

Abstract: A differentiation block with accumulation of immature myeloid cells characterizes acute myelogenous leukemia (AML). However, native AML cells often show some morphological signs of differentiation that allow a classification into different subsets, and further differentiation may be induced by exposure to various soluble mediators, e.g., all trans-retinoic acid (ATRA) and several cytokines. Combination therapy with ATRA and chemotherapy should now be regarded as the standard treatment for the acute promyelocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 98 publications
0
36
0
1
Order By: Relevance
“…2). Induction of blast differentiation and/or apoptosis is an established approach to resolution of human leukemias (Bruserud et al, 2000;Nowak et al, 2009). The ability of EPZ-5676 to cause blast differentiation and apoptosis by itself, and the enhancement of these effects by Ara-C and daunorubicin, bode well for the effective use of this compound alone or with chemotherapy as a clinical treatment for MLL-r patients.…”
Section: Synergy Of Epz-5676 With Aml Soc Inmentioning
confidence: 99%
“…2). Induction of blast differentiation and/or apoptosis is an established approach to resolution of human leukemias (Bruserud et al, 2000;Nowak et al, 2009). The ability of EPZ-5676 to cause blast differentiation and apoptosis by itself, and the enhancement of these effects by Ara-C and daunorubicin, bode well for the effective use of this compound alone or with chemotherapy as a clinical treatment for MLL-r patients.…”
Section: Synergy Of Epz-5676 With Aml Soc Inmentioning
confidence: 99%
“…The major treatment choice is the classical chemotherapy [10]. The M2 AML responds well to high dose cytarabine exhibiting high remission rate and long disease-free survival [57].…”
Section: Treatment Response In Patients With Aml1-etomentioning
confidence: 99%
“…AML is characterized by accumulation of cells at the early stages of the differentiation process [8][9][10]. This is mostly attributed to dysfunctional regulatory transcription factors, resulting in aberrant gene expression and function [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As 2 O 3 was established as a potent alternative in therapy of all-trans retinoic acid (ATRA)-resistant APL and shows, like Sb 2 O 3 , similar cellular effects to ATRA in APL: localization of the t(15;17) specific PML-RARα-fusion protein in nuclear bodies and degradation of the fusion protein [6][7][8][9] and induction of differentiation and apoptosis [10][11][12][13][14]. Lately, we showed that induction of apoptosis by As 2 O 3 in 22 myeloid and non-myeloid malignant cell lines of different sensitivity for cytostatic drugs, is based on breakdown of the mitochondrial membrane potential (Ψ m ) and therefore the redox system of the cell is one of the primary targets of As 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%